The influence of size and distance of Atlantic forest patches on seed rain over tropical pasture - Lorenzon, Pedro Camargo [UNESP]; Massi, Klécia Gili [UNESP] (Springer Nature, 2022)
Atlantic Forest has experienced an expansion of vegetation fragments in abandoned pasture areas. Thus, we aimed to evaluate seed rain over abandoned pasture from two forest patches of the Southeast Atlantic Forest related to distance from the edge and patch size. For eight months, seeds were collected, measured and weighed. Our results showed decreased seed rain (in terms of number, weight and size of seeds) within abandoned pastures with increasing distance from the forest edge and decreasing fragment size. We also found a more diverse and even plant community in the seed rain of small patch and discussed the meaning of these results for pasture regeneration, as the importance of small and large patches as seed sources in a landscape.
Keywords: Distance to edge; Fragment size; Natural regeneration; Seed dispersal; Tropical forest